MODEL ALTMAN Z-SCORE UNTUK MEMPREDIKSI FINANCIAL DISTRESS : STUDI EMPIRIS PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lidya Martha; Sri Mardhatillah; Zusmawati Zus (JURNAL PUNDI, 2017)
Financial distress is the financial difficulties experience by a company before the company become bankruptcy (Mafiroh, 2016). The purpose of this study was to determine which firms would be predicted financial distress. The population in this research is manufacturing companies listed in Indonesia Stock Exchange in 2015. In this study, the population is used 365 companies. The process of collecting samples are using purposive sampling method. The model used to analyze the rate of financial distress is Altman Z-Score Model. The results showed that of the 15 companies that were sampled 5 (five) of them were healthy (>2,99), 2 (two) of them were financial distress (<1,81) and 8 (eight) indicated in grey area (1,81 – 2,99).